Acute Kidney Injury: Controversies Revisited - Kenneth Yong; Gursharan Dogra; Neil Boudville; Mary Pinder; Wai Lim (International Journal of Nephrology)
This paper addresses the epidemiology of AKI specifically in relation to recent changes in AKI classification and revisits the controversies regarding the timing of initiation of dialysis and the use of peritoneal dialysis as a renal replacement therapy for AKI. In summary, the new RIFLE/AKIN classifications of AKI have facilitated more uniform diagnosis of AKI and clinically significant risk stratification. Regardless, the issue of timing of dialysis initiation still remains unanswered and warrants further examination. Furthermore, peritoneal dialysis as a treatment modality for AKI remains underutilised in spite of potential beneficial effects. Future research should be directed at identifying early reliable biomarkers of AKI, which in conjunction with RIFLE/AKIN classifications of AKI could facilitate well-designed large randomised controlled trials of early versus late initiation of dialysis in AKI. In addition, further studies of peritoneal dialysis in AKI addressing dialysis dose and associated complications are required for this therapy to be accepted more widely by clinicians.